2022
DOI: 10.7150/ntno.74613
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Advances in the Detection and Treatment of Cancer: An Overview

Abstract: Over the last few years, progress has been made across the nanomedicine landscape, in particular, the invention of contemporary nanostructures for cancer diagnosis and overcoming complexities in the clinical treatment of cancerous tissues. Thanks to their small diameter and large surface-to-volume proportions, nanomaterials have special physicochemical properties that empower them to bind, absorb and transport high-efficiency substances, such as small molecular drugs, DNA, proteins, RNAs, and probes. They also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 257 publications
(274 reference statements)
0
37
0
Order By: Relevance
“…Polymer nanomaterials have potential in medical treatments and therapies such as imaging, faster diagnosis, and drug distribution, and offer many attractive advantages over conventional drugs, including stability, better bioavailability, minimized toxic side effects, and enhanced drug delivery [ 22 , 45 , 46 ]. Polymeric NPs are capable of combining other functions such as controlled release, imaging agency, targeted delivery, and the loading of more than one drug for combination therapy [ 47 , 48 ].…”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%
“…Polymer nanomaterials have potential in medical treatments and therapies such as imaging, faster diagnosis, and drug distribution, and offer many attractive advantages over conventional drugs, including stability, better bioavailability, minimized toxic side effects, and enhanced drug delivery [ 22 , 45 , 46 ]. Polymeric NPs are capable of combining other functions such as controlled release, imaging agency, targeted delivery, and the loading of more than one drug for combination therapy [ 47 , 48 ].…”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%
“…When compared to the direct administration of chemotherapeutic agents, drug delivery via nanocarriers offers numerous benefits. These benefits include the following: 1) the delivery of drugs that have a low solubility by either enclosing the drugs within the nanocarriers' hydrophobic interfaces or acting as the carriers for the drugs in the blood; 2) lowering chemotherapeutic agents' systemic toxicity; 3) stabilizing their cargo by increasing the biodistribution and pharmacokinetics of the therapeutic agents while reducing renal clearance and extending circulation time owing to drug encapsulation and protection against inactivation by metabolic enzymes; and 4) overcoming drug resistance by selectively targeting cancer cells during nanocarrier uptake via cellular endocytic pathways and simultaneously multiple chemotherapeutic agents are delivered to the tumor while evading the cellular drug efflux pump (Mosleh-Shirazi et al, 2021;Tunç and Aydin, 2022). The most recent findings in nanomedicine that improve OC treatment are presented in the following sections.…”
Section: Nanotechnology Approaches In Oc Treatmentmentioning
confidence: 99%
“…Multiple studies have suggested the use of nanoparticles (NPs) for the prevention, management, and possible treatment of cancer, highlighting their favorable pharmacokinetics, reasonable targeting efficiency, minimal side effects, and limited drug resistance 13,14 . In addition, NPs have shown enhanced performance with unique properties owing to their typical physicochemical advantages, including smaller size, high surface area/volume, ability to allow tumor cells to bind with various functional groups and accumulate at tumor locations 15 . Among the various NPs, metal oxide NPs have shown enormous benefits, such as, non/limited toxicity, cost effective, and antimicrobial/cancer activity, which makes them a promising tool for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition, NPs have shown enhanced performance with unique properties owing to their typical physicochemical advantages, including smaller size, high surface area/volume, ability to allow tumor cells to bind with various functional groups and accumulate at tumor locations. 15 Among the various NPs, metal oxide NPs have shown enormous benefits, such as, non/limited toxicity, cost effective, and antimicrobial/cancer activity, which makes them a promising tool for therapeutic applications. In addition, the therapeutic advantages of metal-oxide NPs are their unique structure, excellent stability, redox and catalytic characteristics, high surface area, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%